2014
DOI: 10.4028/www.scientific.net/amm.618.316
|View full text |Cite
|
Sign up to set email alerts
|

Study on Kinetics of Straw Stalk Gasification in CO<sub>2</sub> with Random Pore Model

Abstract: The gasification of straw stalk in CO2 environment was studied by isothermal thermogravimetric analysis. The characteristics of rice straw and maize stalk gasification at different temperatures were examined under CO2 atmosphere. The relationship between reaction time and carbon conversion of two biomass chars was analyzed by the random pore model (RPM), and compared with the simulation of the shrinking core reaction model (SCRM). The results show that the random pore model is better to predict the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…They concluded that the random pore model had advantages in describing the gasification process of the biomass semichars. Fei and his collaborators also reached a similar conclusion during studying the straw stalk gasification in CO 2 .…”
Section: Thermochemical Conversion Modeling Approachmentioning
confidence: 56%
“…They concluded that the random pore model had advantages in describing the gasification process of the biomass semichars. Fei and his collaborators also reached a similar conclusion during studying the straw stalk gasification in CO 2 .…”
Section: Thermochemical Conversion Modeling Approachmentioning
confidence: 56%
“…These resources are used as fuel, directly or indirectly, avoiding needless burning, burying, or storage [44][45][46], but can also cause extensive environmental pollution when used inefficiently [20,47]. In comparison to other renewable energy options, several studies noted that biomass is abundant in supply from various sources and its energy has the key advantages of being nearly carbon neutral [48][49][50]. The carbon neutrality of biomass resources is dependent on the net CO 2 equivalent greenhouse gases (GHGs) emitted across the entire life cycle processes considered [51], which also involves the emissions generated during the manufacturing and transport phases.…”
Section: Biomass Resourcesmentioning
confidence: 99%